2010
DOI: 10.1111/j.1744-7917.2010.01366.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding-based species delimitation increases species count of Eois (Geometridae) moths in a well-studied tropical mountain forest by up to 50%

Abstract: The genus Eois comprises an important part of megadiverse assemblages of geometrid moths in mountain rainforests of southern Ecuador. In this study we report: (i) on the construction of a DNA barcode library of Eois for identification purposes; and (ii) the exploration of species diversity through species delimitation by pair-wise distance thresholds. COI barcode sequences were generated from 408 individuals (at least 105 species) collected on a narrow geographic scale (∼40 km 2 ) in the Reserva Biológica San … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 41 publications
1
64
0
Order By: Relevance
“…One of the advantages of DNA barcoding with respect to traditional taxonomy is the speed and low costs involved in gathering and analyzing data , Strutzenberger et al 2010. The creation of the CBOL's online database (The Barcode of Life Data System -BOLD: www.barcodinglife.org) has provided an incentive for numerous researchers to join the barcode initiative.…”
Section: Dna Barcoding In Entomologymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the advantages of DNA barcoding with respect to traditional taxonomy is the speed and low costs involved in gathering and analyzing data , Strutzenberger et al 2010. The creation of the CBOL's online database (The Barcode of Life Data System -BOLD: www.barcodinglife.org) has provided an incentive for numerous researchers to join the barcode initiative.…”
Section: Dna Barcoding In Entomologymentioning
confidence: 99%
“…Among these efforts, the use of a short stretch of the mitochondrial cytochrome c oxidase subunit I, popularly known as DNA barcode, has received much attention (Hebert et al 2003a, b, 2004, Janzen et al 2005, Hajibabaei et al 2006, Decaëns & Rougerie 2008, Janzen et al 2009, Strutzenberger et al 2010. Some authors are so partial to this technique that they have implied, or suggested, that DNA barcoding is superior to the classical, morphologically-based taxonomy, and that it should substitute morphology in species descriptions and identification as well as in studies trying to ascertain the relationships between them .…”
Section: Introductionmentioning
confidence: 99%
“…The same situation is reported for two species of parasitoids (Trachyarus solyanikovi and T. fuscipes) (Elzinga et al, 2011a). Strutzenberger et al (2011) even suggest a species specific threshold value of 2% for Eois moths. The lack of universality in divergence thresholds and species level divergence cut-off values has raised questions about whether genetic distance should be included as a component of barcoding in taxonomy (Meyer & Paulay, 2005;Vogler, 2006;Wiemers & Fiedler, 2007).…”
Section: Species Delimitation By Molecular Methodsmentioning
confidence: 48%
“…In the most recent attempt using mitochondrial DNA, Grapputo et al (2005) were unable to completely resolve the phylogenetic relationships due to weak phylogenetic support and lack of correspondence between molecular and morphological methods. Therefore, bagworm moths are good candidates for attempting to identify species using DNA barcoding, since morphological differentiation is minimal (Strutzenberger et al, 2011) and their taxonomy is not optimally resolved (Suomalainen, 1980;Palmqvist, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The large-scale inventory of caterpillars, their hosts and their parasites in Costa Rica has provided an excellent example of how barcoding has changed the basic approach to an inventory project, starting with sampling, processing, identification, analysis, and even changing the approach to publication of results (Janzen et al, 2009;Hallwachs 2011a, 2011b; see also Strutzenberger et al, 2010). In addition to the changes in work flow there have been significant impacts, from finding cryptic species to matching dimorphic males and females, which have substantially improved the quality and depth of the inventory, but also greatly multiplied the number of situations requiring further taxonomic work for resolution.…”
Section: How Does Barcoding Change the Approach To An Inventory?mentioning
confidence: 99%